1992
DOI: 10.1177/095632029200300305
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Ester Prodrugs of Acyclovir

Abstract: SummaryEighteen amino acid esters of the antiherpetic drug, acyclovir, were synthesized as potential prodrugs for oral administration. The esters were examined for in vitro antiviral activity against herpes simplex virus Type 1 (HSV-1). They were found to have less potency than the parent compound. Their efficiencies as prodrugs were evaluated in rats by measuring the urinary recovery of acyclovir. Ten prodrugs produced greater amounts of the parent drug in the urine. The L-amino acid esters were better prodru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(143 citation statements)
references
References 25 publications
5
138
0
Order By: Relevance
“…The aspartyl prodrugs were more chemically stable potentially due to the negatively charged side chain that may hinder hydroxide ion catalysis of the ester bond. The greater stability of the prodrugs at pH 6.0 can be attributed to a lower hydroxide ion concentration and is consistent with previous findings with acyl floxuridine esters (24) and with valacyclovir (25,26). These results also suggest that degradation of the prodrugs is not substantial (<20% for monoesters) over the time course of the uptake experiments conducted at pH 6.0 to provide the proton gradient necessary for PEPT1-mediated uptake.…”
Section: Discussionsupporting
confidence: 79%
“…The aspartyl prodrugs were more chemically stable potentially due to the negatively charged side chain that may hinder hydroxide ion catalysis of the ester bond. The greater stability of the prodrugs at pH 6.0 can be attributed to a lower hydroxide ion concentration and is consistent with previous findings with acyl floxuridine esters (24) and with valacyclovir (25,26). These results also suggest that degradation of the prodrugs is not substantial (<20% for monoesters) over the time course of the uptake experiments conducted at pH 6.0 to provide the proton gradient necessary for PEPT1-mediated uptake.…”
Section: Discussionsupporting
confidence: 79%
“…For example, oligopeptide transporters are responsible for the active absorption of -lactam antibiotics, the ACE inhibitor enalapril, valaciclovir and valganciclovir. The BA of valaciclovir was 5 times higher than that of aciclovir itself due to transport by the intestinal oligopepetide transporter PEPT1 (Beauchamp et al 1992;Swaan & Tukker 1997;Han et al 1998).…”
Section: The Bcs In the Pharmaceutical Development Phasementioning
confidence: 99%
“…Therefore, to reduce the rapid deamination during intestinal absorption, the N4-amino group of the cytosine ring was masked with L-valine in this study. Since previous studies have reported that L-valine may have the optimal combination of chain length and branching at the beta carbon of the amino acid for the intestinal absorption of peptidomimetic drugs (Beauchamp et al 1992;Han et al 1998;Sugawara et al 2000), L-valine was selected to mask the N4-amino group of the cytosine ring in ara-C and subsequently a peptidomimetic prodrug, L-valyl-ara-C was synthesized as illustrated in Figure 1. L-Valyl-ara-C was obtained as white fluffy powder and its purity was ‡ 98% as determined by HPLC.…”
Section: Synthesis Of L-valyl-ara-cmentioning
confidence: 99%